滚齿机数控系统零编程技术的研究 - 舒启林; 蒋广玉; 侯傲 (Jixie chuandong)
NC hobbing machine slams the complex transmission system of the ordinary hobbing machine.The digital control is adopted in each movement of the machine tool axis,the processing accuracy and efficiency of the machining are improved.In the hobbing processing,the specific kinematic relationship between the workpiece and tool is determined according to the parameters of them.And the zero-programming mathematical model of cylindrical gear is established on the analysis of the feasibility study of zero-programming technology,and it plays a crucial role in the zero-programming software development based on IPC+PMAC.The operators don’t need programming and only need to enter related parameter,the software will automatically generate gear processing program in the development system.